Race, ethnicity, and the politics of city redistricting : minority-opportunity districts and the election of Hispanics and Blacks to city councils - Behr, Joshua G., 1967- (SUNY series in African American studies., 2004)
"Why do cities with similar minority populations vary greatly in the adoption of minority-opportunity districts and, by extension, differ in the number of elected Hispanic and black representatives? Through in-depth research of the districting processes of more than 100 cities, Race, Ethnicity, and the Politics of City Redistricting provides the first nationwide study of minority-opportunity districts at the local level. Joshua G. Behr explores the motives of the players involved, including incumbent legislators, Department of Justice officials, and organized interests, while investigating the roles that segregation, federal oversight, litigation, partisan elections, and resource disparity, among others, play in the election of Hispanics and blacks. Behr's book documents - for both theorists and practitioners - the necessary conditions for enhancing minority-opportunity districts at the local level."--Jacket